Affective and cognitive responses to repeated performance feedback across adaptive and maladaptive dimensions of perfectionism. Issue 4 (14th October 2019) - Lo, Alice; Abbott, Maree J.
The study investigated the affective and cognitive responses (including self-beliefs about personality attributes and the level of certainty associated with these beliefs) to the repeated delivery of performance feedback (failure vs. success) across adaptive and maladaptive dimensions of perfectionism. Participants completed questionnaires and a mental rotation computer task, to which they received feedback for. Performance feedback was delivered at Time point 1 (initial) and at Time point 2 (repeated). Results showed that maladaptive perfectionism predicted increased negative affect after initial failure and decreased confidence in self-descriptiveness ratings for negative-related personality attributes after initial success, with these confidence levels further decreasing following repeated success. Adaptive perfectionism predicted higher self-ratings on positive-related personality attributes but only after initial success. The findings suggest that changes in responses across adaptive and maladaptive perfectionism are influenced by experiences of success rather than failure. Adaptive perfectionism also seemed resilient to input from external sources while maladaptive perfectionism appeared more susceptible to such influence. However, given the preliminary nature of the present findings, further research in this area is needed to understand the impact of performance feedback on the self-concept across these two dimensions of perfectionism.